2010
DOI: 10.1056/nejmoa0900928
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of Endobronchial Valves for Advanced Emphysema

Abstract: Endobronchial-valve treatment for advanced heterogeneous emphysema induced modest improvements in lung function, exercise tolerance, and symptoms at the cost of more frequent exacerbations of COPD, pneumonia, and hemoptysis after implantation. (Funded by Pulmonx; ClinicalTrials.gov number, NCT00129584.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
789
5
38

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 715 publications
(859 citation statements)
references
References 36 publications
27
789
5
38
Order By: Relevance
“…Despite these promising findings, such bronchoscopic lung volume reduction (BLVR) has important limitations: valve placement may induce granuloma formation and localized inflammation, with subsequent mucus hypersecretion, which can increase the risk of infection and contribute to worsening of clinical status in these patients 2.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these promising findings, such bronchoscopic lung volume reduction (BLVR) has important limitations: valve placement may induce granuloma formation and localized inflammation, with subsequent mucus hypersecretion, which can increase the risk of infection and contribute to worsening of clinical status in these patients 2.…”
Section: Introductionmentioning
confidence: 99%
“…In US VENT study by Sciurba et al, an EBV was implanted in 214 patients with emphysema, and results indicated that the forced expiratory volume in 1 second (FEV 1 ) increased by 4.3% over the previous procedure in 6 months, compared to a decrease of 2.5% in the control group (p = 0.005). Similar differences were observed in the 6-minute walk test (6MWT) and health-related quality of life measured with the St. George's Respiratory Questionnaire (SGRQ), and the modified Medical Research Council (mMRC) Dyspnea scale (18). In the implantation need to be developed for the technique to be effective.…”
Section: Endobronchial Valves and Intrabronchial Valvesmentioning
confidence: 60%
“…The Endobronchial Valve for Emphysema Palliation Trial, or VENT, was the first and largest randomized controlled trial (RCT) of valve implantation to treat emphysema; the trial was conducted separately in the US and Europe (18,19). In US VENT study by Sciurba et al, an EBV was implanted in 214 patients with emphysema, and results indicated that the forced expiratory volume in 1 second (FEV 1 ) increased by 4.3% over the previous procedure in 6 months, compared to a decrease of 2.5% in the control group (p = 0.005).…”
Section: Endobronchial Valves and Intrabronchial Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…4) aimed at collapsing or shrinking the emphysematous lung tissue have been developed These methods are an option only for patients with advanced stages of the disease and require an exhaustive diagnosis of lung function. Derived from the VENT-study [19], the inclusion criteria comprises, among other factors, stage 3 (through 4) COPD according to GOLD with high-grade pulmonary hyperinflation (residual volumes over 200 %). In principle, distinction must be made between blocking and non-blocking as well as between reversible and irreversible procedures.…”
Section: Endoscopic Lung Volume Reduction (Elvr)mentioning
confidence: 99%